Influence of diagnosis of venous thromboembolism on immature platelets, absolute platelet count and platelet aggregation over time - Wustrow, Isabel; Ebner, Christopher; Langwieser, Nicolas; Haller, Bernhard; Luppa, Peter B.; Bradaric, Christian; Bongiovanni, Dario; Stundl, Anja; Laugwitz, Karl-Ludwig; Ibrahim, Tareq; Bernlochner, Isabell (Platelets, 2021)
The extent of the involvement of platelets in venous thromboembolisms (VTE) is still not fully understood. Immature platelets are large, RNA-rich, prothrombotic platelets. They are involved in arterial thromboembolisms and are associated with adverse cardiovascular events. Their role in VTE has not been investigated before. The aim of this study was to assess different platelet parameters including immature platelet fraction (IPF), immature platelet count (IPC), absolute platelet count and platelet aggregation (PA) over time in patients with VTE at time of diagnosis, as well as at 3–10 days and at 90–110 days after diagnosis. 50 healthy volunteers similar in age and sex to patients served as controls at diagnosis. IPF was measured by the Sysmex XE-5000 analyzer, PA was assessed using the Multiplate analyzer. Diagnosis of VTE had no relevant effect on IPF and IPC whereas absolute platelet count and PA were significantly decreased compared to controls. In the course of VTE, IPF decreased significantly, whereas IPC, absolute platelet count and PA increased. In conclusion, VTE was associated with relevant changes of the absolute platelet count and PA at diagnosis, as well as changes in IPF and IPC over time reflecting a relevant and measurable platelet consumption in VTEs.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Immature platelet count; immature platelet fraction; immature platelets; platelet aggregation; reticulated platelets; venous thrombosis